Australian and New Zealand Guideline for Mild to Moderate Head Injuries in Children. (2nd February 2021) - Babl, Franz E; Tavender, Emma; Ballard, Dustin W; Borland, Meredith L; Oakley, Ed; Cotterell, Elizabeth; Halkidis, Lambros; Goergen, Stacy; Davis, Gavin A; Perry, David; Anderson, Vicki; Barlow, Karen M; et al.
Abstract: Objective: Children frequently present with head injuries to acute care settings. Although international paediatric clinical practice guidelines for head injuries exist, they do not address all considerations related to triage, imaging, observation versus admission, transfer, discharge and follow‐up of mild to moderate head injuries relevant to the Australian and New Zealand context. The Paediatric Research in Emergency Departments International Collaborative (PREDICT) set out to develop an evidence‐based, locally applicable, practical clinical guideline for the care of children with mild to moderate head injuries presenting to acute care settings. Methods: A multidisciplinary Guideline Working Group (GWG) developed 33 questions in three key areas – triage, imaging and discharge of children with mild to moderate head injuries presenting to acute care settings. We identified existing high‐quality guidelines and from these guidelines recommendations were mapped to clinical questions. Updated literature searches were undertaken, and key new evidence identified. Recommendations were created through either adoption, adaptation or development of de novo recommendations. The guideline was revised after a period of public consultation. Results: The GWG developed 71 recommendations (evidence‐informed = 35, consensus‐based = 17, practice points = 19), relevant to the Australian and New Zealand setting. The guideline is presented as three documents: (i) a detailed Full Guideline summarising the evidence underlying each recommendation; (ii) a Guideline Summary; and (iii) a clinical Algorithm: Imaging and Observation Decision‐making for Children with Head Injuries. Conclusions: The PREDICT Australian and New Zealand Guideline for Mild to Moderate Head Injuries in Children provides high‐level evidence and practical guidance for front line clinicians. Abstract : Children with a head injury are frequently evaluated in acute care settings. By adopting or adapting existing international paediatric clinical practice guidelines for head injuries or devising de novo recommendations, a multidisciplinary multistate working group led by the PREDICT network developed 71 recommendations (evidence‐informed = 35, consensus‐based = 17, practice points = 19). The resulting PREDICT Australian and New Zealand Guideline for Mild to Moderate Head Injuries in Children provides high‐level evidence and practical guidance for front line clinicians.